Artificial Insemination and Parthenogenesis in the Zebra Shark Stegostoma tigrinum - Adams, Lance; Lyons, Kady; Larkin, Elizabeth; Leier, Nicole; Monday, Janet; Plante, Chris; Dubach, Jean; Wyffels, Jennifer (Frontiers in Marine Science, 2022)
Maintaining self-sustaining populations of zoo and aquarium collections can be challenged when natural reproduction fails within mixed-sex populations; however, reproductive success can sometimes be restored with the application of reproductive technologies. Among a population of three female and one male Zebra Sharks (Stegostoma tigrinum), production of young failed despite constant male presence with two of the females. To determine if assisted techniques could be used to rescue sexual reproduction, artificial insemination was performed in a singleton female twice over a three-year period using freshly collected semen. Hatching success for eggs laid by all three females was monitored to compare natural and artificial insemination modes. After the first insemination (December 15th, 2011), 143 yolked eggs resulted in no sexually produced offspring and four genetically-confirmed, parthenogenetic offspring. After the second insemination (September 24th, 2013), 62 yolked eggs resulted in two sexually produced offspring, 18 and 33 days after insemination, and three parthenogenetic offspring > 213 days post-insemination. For the two females housed with the male, no sexual offspring resulted. All females produced at least one hatched parthenote. This study successfully employed artificial insemination to circumvent barriers to natural reproduction in Zebra Sharks. With further development, artificial insemination represents a powerful tool that could be used for maintaining genetic diversity for animals housed in aquaria and conservation-based breeding programs for elasmobranchs.